(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The influence of MMEMW on thermostability of DNA and its complexes with Hoechst 33258 in a wide interval of ionic strength of the solution (0.002–0.1 M Na+ ) has been carried out. It is revealed that at low ionic strength of a solution (μ 0.002 M Na+ ) thermostability of DNA and its complexes with Hoechst 33258 at irradiation by MMEMW considerably increases in comparison with nonirradiated samples. Increasing the ionic strength of the solution the thermostability of the irradiated and nonirradiated samples differ very little. It is also revealed that at irradiation the specificity of Hoechst 33258 to АТ-sequences of DNA at high ionic strength is not shown.